Penerapan Tema Arsitektur Perilaku Pada Bangunan Panti Jompo Di Deli Serdang - Sri Wahyuni; Rina Saraswaty; Neneng Yulia Barky (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2022)
The Nursing Home is a place for elderly people who either voluntarily or are handed over by their families to take care of all their needs. A place that will become a haven for the elderly to enjoy their old age by feeling safe and comfortable and getting all the facilities that are adequate and supportive for all their needs and activities. Deli Serdang is one of the areas where the majority of the middle and upper population are busy working to meet their daily needs which in turn affects the elderly so that they receive less attention from family members. Therefore, it is necessary to design a nursing home that can accommodate the middle and upper elderly by paying attention to facilities that ensure the comfort of its users. The nursing home will be located on Jalan Inpres Block Gading, Deli Serdang Regency, North Sumatera using the Behavioral Architecture theme, where all the building designs are based on the behavior of its users, namely the elderly.